Sufficient optimality conditions for a class of epidemic problems with control on the boundary - Miniak-Górecka Alicja; Nowakowski Andrzej (Mathematical Biosciences and Engineering)
In earlier paper of V. Capasso et al it is considered a simply model of controlling an epidemic, which is described by three functionals and systems of two PDE equations having the feedback operator on the boundary. Necessary optimality conditions and two gradient-type algorithms are derived. This paper constructs dual dynamic programming method to derive sufficient optimality conditions for optimal solution as well $ε $-optimality conditions in terms of dual dynamic inequalities. Approximate optimality and numerical calculations are presented too.